PENGARUH PERCEIVED SOCIAL SUPPORT TERHADAP PERSONAL GROWTH INITIATIVE PADA KARYAWAN - Rifda Alda Ufaira; Ria Thalia; Dini Darmayanti; Muhammad Shodikul Haq (Departemen Psikologi, Universitas Negeri Padang, 2026)
This study aims to examine the influence of perceived social support on personal growth initiatives (PGI) in employees. The dynamic changes in the workplace and increasing labor competition require employees to have active self-development initiatives. This study uses a quantitative approach with an explanatory research design. Respondents totaled 139 employees in Indonesia who have worked for at least one year, selected using a convenience sampling technique. The measuring instruments used were the Personal Growth Initiative Scale-II (PGIS-II) from Robitschek et al. (2012) and the Perceived Social Support Scale from Kuriakose et al. (2019). Data analysis used simple regression with IBM SPSS 24.0. The results showed that perceived social support has a positive and significant effect on personal growth initiative (R = 0.328; R² = 0.108; p = 0.000; B = 0.637). This finding indicates that the higher employees' perceptions of social support from supervisors and coworkers, the higher their personal growth initiatives. The effective contribution of perceived social support to personal growth initiative is 10.8%, while the remainder is influenced by other factors. This study suggests that organizations should create a climate of social support to encourage employees to be proactive in self-development.